Watermark blending technique for securing user authentication data in mobile application systems - Mohamed, Kartini; Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
Watermark is traditionally used for protecting copyrighted materials such as scripts, movies, images or sounds. Nowadays, the watermark is still widely used but more in a digitized environment. There are many ways of how the watermarks are being applied. In this paper, the watermark is not applied for the purpose of protecting copyrighted materials but more on digitally securing user authentication data used for accessing mobile application systems (mobile apps). A user authentication model is developed to improve the access control to mobile apps. The model introduces three protection techniques namely multi-factoring, ciphering and watermarking techniques. In multi-factoring technique, the number of user authentication factors is increased from having just username and password to raise the difficulty of guessing the authenticating data. The added factors are mobile IMEI number, mobile SIM card number, random number and time. In ciphering technique, the user authentication factors are not only encrypted but also hashed to ensure the encrypted data cannot be easily decrypted. Finally, in the watermarking technique, the authenticating data are concealed by blending them in such a way that they cannot be un-blended without knowing the blending formula. Although there are three protection techniques introduced, only watermarking technique is described in more details in this paper. The effectiveness of the introduced techniques is measured based on user acceptance level using a statistical analysis. The analysis shows that although ciphering technique is the highest contributor among other techniques, watermarking technique not only has the strongest relationship but also becomes the dominant factor in making them acceptable by users of mobile apps.